Inhalation of nicotine-containing electronic cigarette vapor exacerbates the features of COPD by inducing ferroptosis in βENaC-overexpressing mice - Han, Hongwei; Meister, Maureen; Peng, Guangda; Yuan, Yi; Qiao, Jingjuan; Yang, Jenny J.; Liu, Zhi-Ren; Ji, Xiangming (Frontiers in Immunology, 2024)
Chronic obstructive pulmonary disease (COPD) is currently listed as the 3 rd leading cause of death in the United States. Accumulating data shows the association between COPD occurrence and the usage of electronic nicotine delivery systems (ENDS) in patients. However, the underlying pathogenesis mechanisms of COPD have not been fully understood. In the current study, βENaCoverexpressing mice (βENaC mice) were subjected to whole-body ENDS exposure. ENDSexposed mice displayed enhanced emphysema and mucus accumulation, suggesting that ENDS exposure promotes COPD features. ENDS exposure also increased immune cell number infiltration in bronchoalveolar lavage and levels of multiple COPD-related cytokines in the lungs, including CCL2, IL-4, IL-13, IL-10, M-CSF, and TNF-𝛼. Moreover, we observed increased fibrosis in ENDS-exposed mice, as evidenced by elevated collagen deposition and α-SMA+ myofibroblast accumulation. By investigating possible mechanisms for how ENDS promoted COPD, we demonstrated that ENDS exposure induced cell death of alveolar epithelial cells, evidenced by TUNEL staining and Annexin V/PI FACS analysis. Furthermore, we identified that ENDS exposure caused lipid dysregulations, including TAGs (9 species) and phospholipids (34 species).As most of these lipid species are highly associated with ferroptosis, we confirmed ENDS also enhanced ferroptosis marker CD71 in both type I and type II alveolar epithelial cells. Overall, our data revealed that ENDS exposure exacerbates features of COPD in ENaC mice including emphysema, mucus accumulation, abnormal lung inflammation, and fibrosis, which involves the effect of COPD development by inducing ferroptosis in the lung.